King Edward I's Policy Towards the Jews of England until 1290 AD (Journal of the College of Basic Education, 2025)
This study traces the arrival of Jewish ethnic group in England in conjunction with the Norman conquest in 1066 AD, to make the Jews part of the demographic change that began in England after that conquest, the front before England emerging in the economic influence of the Jews, an element familiar with monetary dealings, especially in the usurious aspect that multiplies the wealth of the Jews at the expense of the simple English and their nobility alike, which mobilized the English against the Jews who changed them socially and religiously, so the Jews became aiming to prevent English attacks whenever they had the opportunity, and this grew with time until the last expulsion of the Jews by the King of England, Edward I, in 1290 AD, which we will uncover its cause, circumstances and results